2018
DOI: 10.3390/su10093136
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Eco-Friendly Binary and Ternary Blended Binders Made of Fly-Ash and Oil-Refinery Spent Catalyst in Ready-Mixed Concrete Production

Abstract: Large-scale recycling of new industrial wastes or by-products in concrete has become a crucial issue for construction materials sustainability, with impact in the three pillars (environmental, social and economic), while still maintaining satisfactory, or improved, concrete performance. The main goal of the paper is to evaluate the technological feasibility of the partial, or total, replacement of fly-ashes (FA), widely used in ready-mixed concrete production, with spent equilibrium catalyst (ECat) from the oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 43 publications
(70 reference statements)
0
14
0
1
Order By: Relevance
“…After several catalytic cycles, the catalysts may become deactivated due to the adsorption of products, byproducts, or the formation of coke, but in many cases, zeolites can easily be reactivated by performing thermal treatments. In addition, when they are exhausted and at the end of their regeneration cycles, they can be used as precursors for producing concrete [11], new adsorbent materials for the withdrawing of pollutants from the environment [12], or even new catalysts [13].…”
Section: Zeolites and Related Materials As Support For The Heterogenization Of The Catalystsmentioning
confidence: 99%
“…After several catalytic cycles, the catalysts may become deactivated due to the adsorption of products, byproducts, or the formation of coke, but in many cases, zeolites can easily be reactivated by performing thermal treatments. In addition, when they are exhausted and at the end of their regeneration cycles, they can be used as precursors for producing concrete [11], new adsorbent materials for the withdrawing of pollutants from the environment [12], or even new catalysts [13].…”
Section: Zeolites and Related Materials As Support For The Heterogenization Of The Catalystsmentioning
confidence: 99%
“…Another study [ 15 ] reported higher heat of hydration values observed in concrete mixes where cement was substituted by 10% of FCCCw (the paper provides test results for specimens modified with 0%, 10% and 35% of FCCCw). Authors [ 16 ] have also found that FCCCw generated in oil refineries in Portugal has pozzolanic properties and can be used in the manufacture of ecological structural concrete. According to the findings reported in other research articles [ 17 , 18 , 19 ], the FCCCw used in the tests definitely had high pozzolanic activity, whereas the binder containing FCCCw demonstrated a higher compressive strength and resistance to chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The recent review by Tang et al [39] shows that the partial substitution of up to 30% by weight of recycled clay waste from CDW as SCM in the manufacture of concrete can improve, if the fineness of the waste is adequate, the properties of new concretes incorporating these new SCMs in the cement with respect to conventional concrete, as well as being an effective solution to mitigate the pollutant emissions associated with cement production, with a reduction of up to 8.1% of cement produced [40].…”
Section: Introductionmentioning
confidence: 99%